Intellectual property rights and food security [ (CABI, 2009)
Intellectual Property Rights (IPRs) play an important role in the struggle for food security and encouraging agricultural research and development. This book examines these roles as well as the international relationship between IPRs, agricultural biotenology, access to biological resources, food security and globalisation.